INVESTIGATION OF THE EFFECT OF RECRYSTALLIZATION ON THE MECHANICAL PROPERTIES OF HIGH-NICKEL ALLOY SHEETS DURING ROLLING - Berdiyev Darob Muratovich,; Saydumarov Botir Muradovich,; Xasanov Kamoliddin Akmal o‘g‘li,; Yuldashaliyev Shohruhbek Diyorbek o‘g‘li, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2026)
The article investigates the effect of the recrystallization phenomenon occurring during the hot rolling of sheet materials made from high-nickel alloys on the mechanical and structural properties of the metal. During the study, the influence of the degree of deformation, rolling temperature, and cooling rate on grain size, strength, and plastic properties was scientifically analyzed. The obtained results are of significant importance for optimizing the sheet rolling technology of high-nickel alloys.